Nursing Roles within a Stroke Telemedicine Network - Kiernan, Terri-Ellen J. (Libertas Academica, 2010)
Time sensitive acute stroke treatments and the growing shortage of vascular neurologists compound to create a gap in the delivery of care to meet the American Stroke Association guidelines in underserviced regions. Audio/video consultation (telemedicine), which has been evolving since the late 1990’s, is a putative solution. While telemedicine can serve as a valuable facilitative tool, the telestroke consultation is only one piece of a complex collaboration between hub and spoke environments and clinical personnel. The growing use of telemedicine in stroke offers more opportunities for all nurses to participate in the continuum of cerebrovascular disease care. A review of this collaboration will include but will not be limited to: algorithms of the acute stroke evaluation, hub and spoke staff meetings, stroke education for spoke staff, and patient follow-up post acute treatment. Our team’s telemedicine experience, utilizing research, education, and clinical practice, will be described.